Pelatihan Manajemen Pemasaran untuk Meningkatkan Kinerja Tim Marketing Mahasiswa - Solechan Solechan; Zahrotun Ni’mah Afif; Beny Sintasari; Mar’atul Azizah; Ainur Rofiq (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
This service aims to provide marketing management training to marketing team students at STIT Al Urwatul Wutsqo Jombang to improve performance in promoting the campus. In the increasingly developing digital era, campus marketing requires the right strategy to reach a wider and more effective audience. This training focuses on increasing students' understanding of basic marketing concepts, the use of social media for promotions, as well as market analysis techniques and effective communication. This training was carried out through a participatory approach involving 20 students as active participants. The method used in this service consists of several stages, namely needs assessment, theoretical training, practicum and simulation, evaluation and feedback. Based on the evaluation results, this training was proven to be able to improve the marketing team's skills in designing and implementing more professional and creative marketing strategies, as well as having a positive impact on achieving campus marketing goals